UPAYA MENINGKATKAN DISIPLIN GURU DALAM KEHADIRAN MENGAJAR DIKELAS MELALUI PENERAPAN REWARD AND PUNISHMENT DI SDN 03 SIMPANG KABUPATEN PESISIR SELATAN - Sulyadi Sulyadi (JURNAL MANAJEMEN PENDIDIKAN, 2018)
ABSTRACT Improving the quality of learning in schools depends on a number of factors. A very important factor, among others, is the application of school culture towards improving quality. School culture is a positive thing that must be maintained and implemented by all school residents without feeling forced. School culture that must be maintained, one of them is discipline, including the discipline of teachers in attendance in the classroom in the teaching and learning process. To improve the discipline of teachers can be pursued through various ways. In this School Action Research (PTS), an action was tried in the form of the application of Reward and Punishment for teachers at SDN 03 Simpang, Pesisir Selatan Regency. This study was carried out in two cycles, because of the results of research and data analysis, it turns out that in the second cycle, the discipline of teachers in attendance in the classroom in the teaching and learning process increases and meets the indicators that have been set at 75%. From the results of this study, it can be concluded that to improve teacher discipline in the presence of class in teaching and learning activities can be done by applying the Reward and Punishment to the teacher.Keywords: Teacher Discipline, Reward and Punishment